Respon Tanaman Kedelai (Glycine max L.) Varietas Anjasmoro Terhadap MOL Bonggol Pisang - Berlian Zetikarya Haryati (AgroSainT, 2019)
The rise in global soybean consumption is not equivalent to Indonesia's increase in soybean production. Enhancing cultivation methods, such as by exploiting local microorganisms, is one option to increase soybean yield in Indonesia (MOL). One of the raw materials for making MOL, which is very simple to find in the Toraja region, is banana weevil. Carbohydrates, which aid in the development of microbes, are abundant in the banana weevil. This study set out to discover how soybean plants (Glycine max L.) reacted to banana weevil feeding. A randomized block design (RBD) was used to conduct the study. There were 5 treatment levels: B0 (control), B1 150 cc/l water, B2 300 cc/l water, B3 450 cc/l water, and B4 600 cc/l water. The outcomes demonstrated that the soybean plants responded well to the banana weevil treatment. The plants that produced the maximum amount (379.93 g per plot, or 2.1 tons/ha) in response to the banana weevil MOL with a dose of 600 cc/l water were those that produced the most of that substance.